ENGINEERING ON-LINE LEARNING WITH CCTV LIVE-STREAMING WEB BASED OPEN SOURCE - Supriyanto, Aji (Jurnal Ilmiah Informatika Komputer, 2008)
Effectiveness media for learning activity is not enough only utilize the traditional media method, such as classical activity by using white board. Development of communication and computer technology can support long distance study by using network, server or web or by live interaction such as live streaming.Development of live-streaming in education activity is not only by using teleconference that need handshaking connection. Other model is by using web based CCTV live-streaming that use open source software. The web based model is more efficient then teleconference, the main reason does not need handshaking connection. The all web browser can be as client which can directly access multimedia document. Result of the research is an alternative learning on-line live-streaming model by utilize web server and open source.Key words: CCTV, learning activity, live-streaming, web.Subject Description : H.4.Information Systems Applications | H.4.3. Communication Applications | Computer Conferencing, Teleconferencing and Video Conferencing